THE IMPACT OF CULTURAL DIVERSITY ON TEAM PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY OUTCOMES IN NIGERIA MULTINATIONAL COMPANIES - Adedeji, Adebowale J.; Zhang, Jie; Redchikova, Nataliya A. (International Journal of Research -GRANTHAALAYAH, 2025)
Nigeria is a country characterized by its vast ethnic and cultural diversity. As a result, multinational companies face the challenge of managing teams composed of individuals from diverse cultural backgrounds. This paper examined the impact of cultural diversity on team performance and corporate social responsibility outcomes in Nigerian multinational companies. A descriptive survey design was employed to conduct the study. The study adopted a quantitative research design to examine the challenges of managing cultural diversity in multinational companies (MNCs). The study focused on employees and managers in multinational companies operating in Nigeria, particularly those with diverse cultural workforces. A stratified random sampling technique was used to select 200 participants. A structured survey questionnaire was developed to collect quantitative data. The survey consisted of closed-ended questions using Likert scale items. Data from the surveys were analyzed using descriptive statistics to describe the distribution of responses. Inferential statistics examined the relationships between cultural diversity challenges and organizational outcomes. The paper proved that cultural diversity was seen as beneficial for CSR effectiveness. Challenges such as communication barriers and potential conflicts are acknowledged, and there is also a strong belief that when managed effectively, cultural diversity can drive innovation, competitive advantage, and employee satisfaction.